2020
DOI: 10.1128/jvi.00147-20
|View full text |Cite
|
Sign up to set email alerts
|

Oregano Oil and Its Principal Component, Carvacrol, Inhibit HIV-1 Fusion into Target Cells

Abstract: Oregano essential oil has long been known for its health-promoting benefits. Here, we report its activity against viral replication. Oregano oil was found to specifically inhibit lentiviruses, such as human and simian immunodeficiency viruses (HIV and SIV), irrespective of virus tropism, but not hepatitis C virus, adenovirus 5 (ADV5), Zika virus, and influenza (H1N1) virus. Oregano oil’s most abundant components, carvacrol and its isomer, thymol, were shown to block virus-target cell fusion while not perturbin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 55 publications
(70 reference statements)
0
38
0
3
Order By: Relevance
“…The study concluded that EOs in vapour form could benefit people suffering from influenza (Vimalanathan and Hudson 2014 ). Carvacrol and its isomer thymol obtained from oregano have been shown to inhibit viral host cell fusion via depletion of viral cholesterol from the HIV-1 envelope membranes, thus blocking the entry of the virus into the host system (Mediouni et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The study concluded that EOs in vapour form could benefit people suffering from influenza (Vimalanathan and Hudson 2014 ). Carvacrol and its isomer thymol obtained from oregano have been shown to inhibit viral host cell fusion via depletion of viral cholesterol from the HIV-1 envelope membranes, thus blocking the entry of the virus into the host system (Mediouni et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that while Pma1p inhibition by CAR is observed to occur and may contribute to the antifungal activity, additional mechanisms of fungal toxicity may be utilized for CAR, including disrupted ergosterol biosynthesis, increased membrane permeability and fluidity, and disrupted cationic gradients across the cell membrane [ 13 , 40 , 41 ]. CAR has also recently found to alter the cholesterol content of the HIV-1 viral membrane, blocking HIV-1 entry into target cells [ 42 ]. The extent to which WSCP1 can carry out these types of effects remains to be investigated but is anticipated, at least to some extent, based on its prodrug status and structural similarity to CAR.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the former EOs have a significant inhibitory effect against vesicular stomatitis virus (VSV), and the Cyperus EO inhibited the Coxsackie B4 virus [ 25 , 26 ]. The EO of tea tree (Melaleuca alternifolia) comprising terpinene-4-ol, limonene, γ- and α-terpinene, cineol, and α-terpinolene and the volatile oil (VO) of Cymbopogon citratus have strongly inhibited the oral and genital herpes viruses [ 29 , 30 ], and the oregano EO rich with monoterpenic phenol, carvacrol (5-isopropyl-2-methylphenol), and its isomeric analoge thymol (2-isopropyl-5-methylphenol) derived from Origanum vulgare plant showed a potent protective effect against human and simian immunodeficiency viruses (HIV and SIV) [ 31 ], and the oxygenated and unoxygenated monoterpenes and sesquiterpenes rich herbal Hornstedtia bella EO [ 27 ], and a monocyclic sesquiterpene, germacrene rich Rhizoma curcuma EOs [ 28 ] have inactivated the vaccinia and pseudorabies virus, respectively. Furthermore, the aglycones molecules especially, quercetin, myricetin, and quercetagetin, and flavonoids such as apigenin, baicalein, biochanin A, kaempferol, luteolin, and naringenin have exhibited broad-spectrum antiviral activity towards a wide range of enveloped (HBV, HCV, HIV, African swine fever, influenza A, dengue, respiratory syncytial and Newcastle disease (NDV)) and non-enveloped (foot and mouth disease and enterovirus) viruses [ 32 ].…”
Section: Emulsion Components Delivering Antiviral Activitymentioning
confidence: 99%
“…The NL4-3 strain achieved resistance through mutations in the envelope glycoprotein, particularly a single-point silent mutation in gp120 protein residues, Ala578Thr mutation in the gp41 residue’s pocket-forming domain in the N-terminal heptad repeat, and Ala839Thr mutation in the cytoplasmic tail domain of gp41. Depending on the number of mutations in the envelope glycoproteins, the resistance level towards carvacrol increased [ 31 ]. Similarly, chicoric acid, a major component present in the Ocimum basilicum and Echinacea purpurea turns out to be ineffective against the NL4-3 strain upon 3 months exposure at low concentration.…”
Section: Development Of Virus Resistance Against Oil Componentsmentioning
confidence: 99%